Intelligent system design for identification of unbalance and misalignment using Fuzzy Logic methods - Romahadi, Dedik; Feriyanto, Dafit; Anggara, Fajar; Wijaya, Fathoni Putra; Dong, Wang (Universitas Mercu Buana, 2024)
Vibration analysis identifies emerging vibration problems before they become unmanageable and cause unforeseen delays. This can be accomplished by monitoring engine vibration continuously or at specific intervals. Unbalance is a common vibration issue caused by the center of mass shifting from the center of rotation, leading to misalignment and excessive vibration between shafts. To prevent this, manual monitoring is required, but it is time-consuming. Therefore, intelligent system monitoring is necessary to save time. Using a large amount of vibration, spectrum, and phase data as input, this project aims to develop a diagnostic application for motor problems based on vibration signals. Fuzzy logic is implemented in MATLAB software to process a considerable amount of input data for all vibrations, spectrums, and phases using the fuzzy logic method. A vibration meter is used to collect vibration data from the demonstration machine. All input data will be processed by the fuzzy system based on predefined fuzzy rules that must provide accurate results for the actual operating conditions of the demonstration machine. Conducting experiments will help the intelligent system correctly detect damage from misalignment and imbalance. The intelligent fuzzy logic system can accurately diagnose damage caused by misalignment and unbalance on the demonstration machine.